The derivative \( f'(1) \) is defined as:
\[
f'(1) = \lim_{h \to 0} \frac{f(1 + h) - f(1)}{h}.
\]
We are given the following condition:
\[
\lim_{h \to 0} \frac{1}{h} f(1 + h) = 5.
\]
Next, decompose the limit expression:
\[
\lim_{h \to 0} \frac{1}{h} f(1 + h) = \lim_{h \to 0} \left( \frac{f(1 + h) - f(1)}{h} + \frac{f(1)}{h} \right).
\]
For the limit to exist and be finite, it must be true that \( \frac{f(1)}{h} \to 0 \) as \( h \to 0 \). This implies:
\[
f(1) = 0.
\]
Now substitute \( f(1) = 0 \) into the equation:
\[
\lim_{h \to 0} \frac{1}{h} f(1 + h) = \lim_{h \to 0} \frac{f(1 + h) - f(1)}{h} = f'(1).
\]
Thus, we find:
\[
f'(1) = 5.
\]
Final Answer:
\[
\boxed{5}
\]